2019
DOI: 10.1021/jacs.8b13899
|View full text |Cite
|
Sign up to set email alerts
|

Strong and Confined Acids Enable a Catalytic Asymmetric Nazarov Cyclization of Simple Divinyl Ketones

Abstract: We report a catalytic asymmetric Nazarov cyclization of simple, acylic, alkyl-substituted divinyl ketones using our recently disclosed strong and confined imidodiphosphorimidate Brønsted acids. The corresponding monocyclic cyclopentenones are formed in good yields and excellent regio-, diastereo-, and enantioselectivities. Further, the chemical utility of the obtained enantiopure cyclopentenones is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…The Nazarov reaction consists in the electrocyclization of divinyl ketones to cyclopentenones through a 4π conrotatory mechanism promoted by Bronsted (BA) or Lewis acids (LA). Many versions of such protocol have been recently developed, both in terms of substrates suitable for cyclization [6] and promoters, including transition metals catalysts [7][8][9][10][11], organocatalysts [12][13][14][15], and UV irradiation (photo-Nazarov reaction) [16].…”
Section: Introductionmentioning
confidence: 99%
“…The Nazarov reaction consists in the electrocyclization of divinyl ketones to cyclopentenones through a 4π conrotatory mechanism promoted by Bronsted (BA) or Lewis acids (LA). Many versions of such protocol have been recently developed, both in terms of substrates suitable for cyclization [6] and promoters, including transition metals catalysts [7][8][9][10][11], organocatalysts [12][13][14][15], and UV irradiation (photo-Nazarov reaction) [16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there is much focus on organocatalyzed systems as environmentally benign, easy-to-handle alternatives to the hazardous reagents employed in conventional Nazarov cyclization conditions. [27][28][29][30][31][32][33][34][35][36][37][38][39] For examples, Tius and colleagues reported an elegant cooperative asymmetric organocatalysis via imine intermediates as activated carbonyl groups. [30][31][32][33] As another case, Matlin's group demonstrated a hydroxylaminecatalyzed reaction based on density functional theory (DFT) analysis of the reaction pathway.…”
Section: Introductionmentioning
confidence: 99%
“…37) Quite recently, an enan-tioselective Nazarov reaction catalyzed by an axially chiral boron reagent was established by Oestreich and colleagues. 38) Our group also attempted to develop a novel catalytic system for the Nazarov cyclization with amine reagents, aiming at efficient activation of the carbonyl group. Unexpectedly, we found that a novel combination of the bench-stable 2,2′-biphenol with the inexpensive, nontoxic, and eco-friendly reagent B(OH) 3 promoted the cyclization of not only activated α-alkoxy divinyl ketones but also inactivated divinyl ketones.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Given the possibility of generating multiple stereocenters in the cyclization, significant effort has also been devoted to the development of asymmetric, catalytic variants, with early successes achieved with certain classes of highly activated dienones, [13] and more recent breakthroughs in cyclizations of electronically unactivated dienones reported by Rawal and List. [14] Herein, we describe enantioselective Nazarov cyclizations of unactivated dienones catalyzed by the combination of a chiral squaramide (3 a) and trimethylsilyl triflate (TMSOTf). On the basis of kinetic isotope effect and other mechanistic studies, an unanticipated basis for enantioinduction is proposed, with the reaction proceeding via reversible electrocyclization and rate-and enantiodetermining proton transfer.…”
mentioning
confidence: 99%
“…[15] A systematic survey of potential model substrates for HBD/TMSOTf co-catalyzed Nazarov reactions led to identification of the diaryl-substituted dienone 1 a as a promising and previously unstudied class of dienones for the HBD/TMSOTf co-catalyzed asymmetric Nazarov cyclization ( Figure 2). [13,14] Multiple factors had to be taken under consideration in the reaction optimization, including not only maximization of product yield and enantioselectivity, but also minimization of byproduct formation, overcoming product inhibition due to TMSOTf binding to the ketone product, and avoidance of product racemization. The structure of the HBD and Lewis acid were naturally critical, with squaramide 3 a and TMSOTf proving optimal (see Table S11 for full catalyst optimization studies).…”
mentioning
confidence: 99%